Pelatihan Pengkabelan Jaringan Komputer sebagai Media Pembentukan Kolaborasi Kemandirian Teknologi dan Harmoni Sosial Keagamaan Sekolah - Melda Agnes; Natasya Leuwol; Amelian Amelian; Brian Brian; Semuel Matatula; Sonya Sonya; Amida Amida; Tabita Tabita; Reynerd Reynerd (Lembaga Pengembangan Kinerja Dosen, 2026)
The training on computer network cabling conducted in schools serves not only to enhance students’ technical competencies but also functions as a strategic medium for developing collaborative attitudes, technological independence, and religious social harmony. Based on the community service activities carried out at SMA Negeri 3 Kota Sorong, the training integrated LAN cabling practice, the introduction of network devices, and guided sessions through observation, socialization, practicum, and evaluation. Throughout these stages, students gained direct experience in crimping, attaching RJ-45 connectors, testing cables with LAN testers, and simulating network configurations, which collectively strengthened their technical mastery. From the perspective of the sociology of religion, the training created a shared learning environment where students of diverse religious backgrounds collaborated equally in completing collective technical tasks. Values such as mutual respect, cooperation across differences, and social solidarity were visibly demonstrated as students helped one another in solving cabling-related challenges. Evaluation results indicate that participants became more independent in completing technical tasks and more open in communicating and interacting with peers of different beliefs. These findings emphasize that technology training can serve as a constructive medium for fostering religious social harmony and character building through practical experiences and meaningful social interaction.